Trends in Liver and Skin Tumor Prevalence in Brown Bullhead (Ameiurus nebulosus) from the Anacostia River, Washington, DC, and Nearby Waters. (February 2019) - Pinkney, Alfred E.; Harshbarger, John C.; Rutter, Michael A.; Sakaris, Peter C.
The prevalence of liver and skin tumors in brown bullhead ( Ameiurus nebulosus ) from the Anacostia River (Washington, DC) and nearby areas was determined in 2014, 2015, and 2016. The objectives were to (1) compare tumor prevalence across space and time; (2) analyze the 1992–2016 Chesapeake Bay Tumor Database to identify reference locations and test age, length, weight, and sex as covariates; and (3) explore whether changes in bullhead exposure to contaminants can explain the observed trends. With logistic regression, we reported large statistically significant decreases in liver tumor probabilities in bullheads from the Anacostia CSX Bridge (ANAC) area between 1996 and 2001 (merged: female, 77.8%; male, 48.6%), 2009 to 2011 (female, 42.5%; male, 16.6%), and 2014 to 2016 (female, 18.0%; male, 5.7%). Skin tumors decreased by a factor of six in both females and males. Polycyclic aromatic compounds (PAC) initiate liver neoplasms and polychlorinated biphenyls (PCBs) and DDT compounds are promoters. The causes of skin tumors in bullhead are uncertain. Biomarker and tissue data show decreases in PAC-DNA adducts and PCB and DDT contamination in ANAC bullheads. It is likely that the decreased liver tumor prevalence is associated with decreased exposure to these contaminants.